PENERAPAN MEDIA LCD PROYEKTOR PADA PEMBELAJARAN IPS KELAS VIII A SMP ISLAM AL-ASY’ARIYYAH PONTIANAK - Amin, Muhammad; Khosmas, Aminuyati; Khosmas, F.Y. (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to determine how the application of LCD projector learning media on social studies subjects in class VIII A Al-Asy'ariyyah Islamic Middle School in North Pontianak. The research method used is descriptive in the form of qualitative research. The primary data sources in this study were teachers and students at Al-Asy'Ariyyah Islamic Middle School in North Pontianak, while secondary data sources in this study were documents or recapitulated values given by the teacher. Research results Learning using conventional methods is considered less effective because there are many obstacles faced by the teacher and also the material explained by the teacher does not reach the learning objectives to be achieved. As for the implementation of learning using LCD media this projector is very effective in attracting students' attention to focus during learning. This is evidenced by the increase in student learning outcomes before and after using LCD Projector learning media. Before using the LCD projector media the average pre-test value of class VIII A students was 53.57. Whereas after using the LCD Projector media the average scores of class VIII A students' tests increased to 78.21. This shows that the application of LCD projector learning media on social studies subjects in class VIII A of Al-Asy'ariyyah Islamic Middle School in North Pontianak can improve student learning outcomes. Keywords: Application, LCD Media Projector, Learning Outcomes